Consequences of Law General Meeting of Shareholders of Closed Companies Through Teleconference - Sonia Jayanto; M. Sudirman; Wira Franciska; Yuhelson (Global Scientific Publishing, 2023)
Since the Covid-19 pandemic in Indonesia, the conduct of the General Meeting of Shareholders (GMS) conventionally had to switch to electronic means, but the Notary Public Act had not yet regulated the electronic issuance of acts, while the Limited Liability Company Act had already regulated GMS through teleconference media, specifically for publicly listed companies in the Financial Services Authority Regulations. However, for closed companies, there is no regulation regulating the mechanism for organizing GMS through electronic means. The purpose of this study is to analyze the legal consequences of a closed company's GMS held through teleconferencing. The method used in this study is normative legal research. The conclusion of this study is that the legal consequence of a closed company's GMS held through teleconferencing is that the GMS becomes invalid and cannot be used as the basis for the process of the next GMS agenda
Keywords: Meeting General Shareholders; Teleconference; Limited Liability Company